Removal of Hazardous Methylene Blue from Aqueous Solutions by Green Citrus Mold (Penicillium digitatum)@Chitosan Hydrogel Beads - Erol Pehlivan; Şerife Parlayıcı (Pharmata)
Objective: This research focuses on the novel technique of using green citrus mould (GCM), namely Penicillium digitatum, in conjunction with chitosan (Ctsn) as a composite to extract Methylene Blue (MB) from aqueous solutions and the composite-dye interactions were assessed analytically.Methods: FT-IR and EDX were used to analyze the chemical characteristics of the adsorbent surface. SEM was used to visualize surface morphology. Kinetic studies were carried out for the removal of MB dye from aqueous solution with the synthesized biosorbent, equilibrium isotherms were derived and adsorption mechanism was investigated. The isotherm parameters of biosorption were determined using the most widely used adsorption models.Results: Qmax value of Green Citrus Mold @Chitosan Hydrogel Beads (GCM@Ctsn) from Langmuir isotherm parameters was calculated as 60.24 mg/g. The dosage of adsorbent that performed optimally was found to be 2 g/L. The pH range, between pH 6 and pH 8, was shown to be the optimal range for attaining optimum removal effectiveness. The thermodynamic data indicated that an exothermic, spontaneous reaction occurred between the MB molecules and the composite. Conclusion: The results highlight the feasibility and usefulness of this environmentally friendly water treatment method by demonstrating its effectiveness.